Examining the learning objectives related to sustainable development in high school physics curricula vis-à-vis the sustainable development goals and revised Bloom’s taxonomy - ERDEMIR, Mustafa (Research Square Platform LLC, 2024)
Abstract This study determines and classifies the learning objectives related to sustainable development (SD) in the physics curricula of the 9th, 10th, 11th, and 12th grades in line with the sustainable development goals set by the United Nations (UN) and Revised Bloom’s Taxonomy (RBT). The classification of learning objectives in line with RBT revealed that these objectives only focus on the cognitive domain, and no learning objectives considering the affective and psychomotor domains were present in the curriculum. Regarding the levels of cognitive learning, the objectives were mainly related to applying, analyzing, and evaluating. The classification of objectives in line with the SD goals showed that the objectives were mostly concerned with the economic pillar of sustainability, followed by the environmental and social pillars. The study concludes that SD-related learning objectives in the physics curriculum are related to the cognitive domain rather than the affective and psychomotor domains.
Keywords: 4. Education; 11. Sustainability; 12. Responsible consumption